The boy who stopped time - Taber, Anthony (New York : Margaret K. McElderry Books, Macmillan Publishing Comp, 1993)
Julian stops the pendulum from swinging on the clock and has a marvelous adventure while the rest of the world is suspended in time.
Keywords: Time -- Fiction; Clocks and watches -- Fiction